A new nano-photocatalyst based on Pt and Bi co-doped TiO2 for efficient visible-light photo degradation of amoxicillin. (2nd January 2019) - Salimi, Maryam; Behbahani, Mohammad; Sobhi, Hamid Reza; Gholami, Mitra; Jonidi Jafari, Ahmad; Rezaei Kalantary, Roshanak; Farzadkia, Mahdi; Esrafili, Ali
Abstract : Herein, the photo degradation of amoxicillin (AMX) was thoroughly investigated using Pt and Bi co-doped TiO2 photocatalysts under visible-light irradiation. Abstract : Herein, the photo degradation of amoxicillin (AMX) was thoroughly investigated using Pt and Bi co-doped TiO2 photocatalysts under visible-light irradiation. The photocatalyst composites were prepared and then characterized by XRD, SEM, EDX, diffuse reflectance spectra (DRS), XPS and N2 sorption-desorption techniques. Amongst the prepared photocatalysts, 1Pt–5Bi–TiO2 exhibited a photo-enhanced activity for the degradation of AMX under visible-light irradiation. The photo degradation efficiency was found to be 87.67% for this composite photocatalyst. The enhancement in the photocatalytic activity is mainly attributed to the formation of photo-generated holes (h + ) and superoxide radicals (O2 ˙ − ), which was confirmed by quenching experiments. These results indicate that the integration of Bi and Pt in the TiO2 structure can efficiently enhance the photocatalytic activity of the used composite.